2017
DOI: 10.1002/2016gc006761
|View full text |Cite
|
Sign up to set email alerts
|

The North America mid‐Cretaceous kimberlite corridor: Wet, edge‐driven decompression melting of an OIB‐type deep mantle source

Abstract: Thirty new high‐precision U‐Pb perovskite and zircon ages from kimberlites in central North America delineate a corridor of mid‐Cretaceous (115–92 Ma) magmatism that extends ∼4000 km from Somerset Island in Arctic Canada through central Saskatchewan to Kansas, USA. The least contaminated whole rock Sr, Nd, and Hf isotopic data, coupled with Sr isotopic data from groundmass perovskite indicates an exceptionally limited range in Sr‐Nd‐Hf isotopic compositions, clustering at the low ɛNd end of the OIB array. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 110 publications
0
15
0
Order By: Relevance
“…It has been tentatively suggested that subduction may have occurred outboard of Baltica at around 800 Ma (e.g., Merdith et al., 2017; Merdith et al., 2021). However, there is no evidence for inboard subduction contemporaneous with the Kuusamo or younger Kaavi‐Kuopio kimberlites (discussed below) which is at odds with examples of kimberlites from North America where subduction is thought to have played some role in their genesis (e.g., Currie & Beaumont, 2011; Duke et al., 2014; Kjarsgaard et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been tentatively suggested that subduction may have occurred outboard of Baltica at around 800 Ma (e.g., Merdith et al., 2017; Merdith et al., 2021). However, there is no evidence for inboard subduction contemporaneous with the Kuusamo or younger Kaavi‐Kuopio kimberlites (discussed below) which is at odds with examples of kimberlites from North America where subduction is thought to have played some role in their genesis (e.g., Currie & Beaumont, 2011; Duke et al., 2014; Kjarsgaard et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…period between 90 and 60 Ma. They are slightly younger than 115-92 Ma kimberlite fields within the North American mid-Cretaceous corridor [Kjarsgaard et al, 2017], and older than the Montana alkaline province intrusions (Sweet Grass Hills minettes; ~50 Ma) [Buhlmann et al, 2000]. The majority of kimberlites occur within the BHH cluster and were emplaced during two intervals at 88-81 Ma (n=10) and 68-60 Ma (n=4 ; Table S1); the older intrusions are diamondiferous (Table S1).…”
Section: Text S4 Kimberlite Emplacement Agementioning
confidence: 97%
“…no garnet). The Somerset Island kimberlites were emplaced 93-98 Ma ago 21 . The smaller suite from Pelly Bay consists of one spinel lherzolite and two garnet-spinel lherzolites and two garnet lherzolites and is a subset of samples investigated by Liu et al 9 where they also focused on PGE geochemistry and Re-Os dating.…”
Section: Peridotite Xenolith Samples a Total Of 30 Peridotitementioning
confidence: 99%